Study of Primary and Secondary Metabolites of Stenospermocarpic, Parthenocarpic and Seeded Raisin Varieties - Ozkan Kaya; Fadime Ates; Zeki Kara; Metin Turan; Gastón Gutiérrez-Gamboa (Horticulturae, 2022)
(1) Background: Stenospermocarpic (Sultani Çekirdeksiz and Black Kishmish), parthenocarpic (Black Corinth), and seeded varieties (Ekşi Kara and Gök Üzüm) are used for raisin production. To our knowledge, there is little available information about the biochemical characteristics of raisins produced from these varieties. (2) Methods: Some metabolites, such as hormones, sugars, vitamins, minerals, and amino acids, including enzymatic activity, were determined in different raisin varieties. (3) Results: Seedless raisin varieties presented higher content of several hormones, vitamins, and minerals, as antioxidant capacity than the raisins produced from seeded varieties. Contrary to this, seeded raisin varieties presented higher contents of most measured sugars and amino acids than the raisins produced from seedless varieties. (4) Conclusions: Biological mechanisms of pollination and fertilization induced modifications in the primary and secondary metabolism of grapes, considerably affecting biochemical compounds and the antioxidant capacity of raisins.